Optimal Sensor Suite Selection for Helicopter Enhanced Vision in All-Weather-All-Environment Operation Using Multi Criteria Decision Making Techniques (Nigerian Journal of Technology, 2021)
Optimum sensor selection for helicopter enhanced vision in all-weather operations is a strategic issue and has a significant impact on safety, efficiency and utility of military and Emergency Service Helicopters. On the other hand, selecting the optimal sensor among many alternatives is a multi-criteria decision-making (MCDM) problem. The sensor selection task in this paper is modelled as a stepwise Analytic Hierarchy Process (AHP) to guide the selection process, based on criteria relating to environmental conditions (fog, rain, dust) and sensor characteristics (detection range, update rate, resolution). Result of this study reveals that a combination of millimeter wave radar, passive millimeter wave camera and infrared camera is the optimal suite having the highest value among all the alternatives considered. This result will guide decision makers at the Headquarters of the Nigerian Air force and indeed other helicopter operators in their quest to equip helicopters for operation in adverse weather conditions.